Effect of heating scheme on SOL width in DIII-D and EAST. (August 2017) - Wang, L.; Makowski, M.A.; Guo, H.Y.; Leonard, A.W.; Xu, G.S.; Gong, X.Z.; Garofalo, A.M.; Deng, G.Z.; Petrie, T.W.; Thomas, D.; Jackson, G.; Kramer, G.; et al.
Highlights: This work presents the effect of heating scheme (RF/NB heating) on the SOL width for the first time, based on the joint DIII-D/EAST divertor experiment. The results in this paper can provide important information for ITER which will be operated in dominant RF-heating scheme for long pulse operation. Abstract: Joint DIII-D/EAST experiments in the radio-frequency (RF) heated H-mode scheme with comparison to that of neutral beam (NB) heated H-mode scheme were carried out on DIII-D and EAST under similar conditions to examine the effect of heating scheme on scrape-off layer (SOL) width in H-mode plasmas for application to ITER. A dimensionally similar plasma equilibrium was used to match the EAST shape parameters. The divertor heat flux and SOL widths were measured with infra-red camera in DIII-D, while with divertor Langmuir probe array in EAST. It has been demonstrated on both DIII-D and EAST that RF-heated plasma has a broader SOL than NB-heated plasma when the edge electrons are effectively heated in low plasma current and low density regime with low edge collisionality. Detailed edge and pedestal profile analysis on DIII-D suggests that the low edge collisionality and ion orbit loss effect may account for the observed broadening. The joint experiment in DIII-D has also demonstrated the strong inverse dependence of SOL width on the plasma current in electron cyclotron heated (ECH) H-mode plasmas.